2020
DOI: 10.1186/s12954-020-00406-y
|View full text |Cite|
|
Sign up to set email alerts
|

An exploratory non-randomized study of a 3-month electronic nicotine delivery system (ENDS) intervention with people accessing a homeless supported temporary accommodation service (STA) in Ireland

Abstract: Background Smoking is endemic amongst people accessing homeless services, and they are disproportionately affected by smoking-related diseases. This paper reports on the results of a 3-month small scale intervention which explored the efficacy, challenges and opportunities of using electronic nicotine delivery systems (ENDS) to support cessation of tobacco smoking with people accessing an Irish supported temporary accommodation (STA) homeless service. It considers the results of this intervention with referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…Over half of the participants reported not knowing the nicotine concentration in their e-cigarettes. Most studies that explored e-cigarette use among PEH have focused on their motivations of use, the effects of e-cigarettes on smoking cessation or subjective experiences of use of e-cigarettes [ 8 , 25 , 26 ]. It is unknown whether the knowledge of nicotine concentration could be associated with the use of e-cigarettes for smoking cessation among PEH and this relationship warrants further exploration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over half of the participants reported not knowing the nicotine concentration in their e-cigarettes. Most studies that explored e-cigarette use among PEH have focused on their motivations of use, the effects of e-cigarettes on smoking cessation or subjective experiences of use of e-cigarettes [ 8 , 25 , 26 ]. It is unknown whether the knowledge of nicotine concentration could be associated with the use of e-cigarettes for smoking cessation among PEH and this relationship warrants further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, a cluster feasibility study of an intervention that provided e-cigarettes for smoking cessation to PEH showed an increased abstinence at 6 months in the intervention group (9% intervention compared to 0% in control) [ 24 ]. An uncontrolled trial of a small-scale intervention of e-cigarettes for smoking cessation showed improvements in self-reported reduction in consumption at a 12-weeks follow-up, but not in expired carbon monoxide among PEH in Ireland [ 25 ]. In the US, a single arm trial of an intervention that included e-cigarettes among cigarette smokers who had experienced homelessness showed an 18% increased odds of being abstinent for each week enrolled in the study [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Author details 1 School of Health Science, Waterford Institute of Technology, Waterford, Ireland. 2 University of California San Francisco, San Francisco, USA.…”
Section: Efficacymentioning
confidence: 99%
“…Following publication of the original article [1], an error was identified in the Table 1 and in the first paragraphs of both Results and Efficacy sections. The correct table and paragraphs are given below.…”
mentioning
confidence: 99%
“…The average length of follow up was 20 weeks, ranging from 4 weeks 38 and 52 weeks. 39 Studies took place in homeless services; 25,[27][28]36 drug treatment services; 35,37,39 outpatient 24,26 prison; 34 a gay health clinic; 29 a community health clinic 30 and a veteran health clinic. 38…”
Section: Summary Of Uncontrolled Trialsmentioning
confidence: 99%